Analysis of Ta'zir Crimes on Decision No. 75/Pid.Sus TPK/2023/PN Jkt.Pst Concerning the Crime of Money Laundering - Fajar Satriyawan Wahyudi; Muhammad Irkham Firdaus; May Shinta Retnowati; Ainun Amalia Zuhroh (AHKAM, 2026)
Corruption in the taxation sector, as reflected in Decision Number 75/Pid.Sus-TPK/2023/PN Jkt.Pst, constitutes an economic crime with systemic impacts that threatens the stability of state finances, in line with the increasing number of corruption cases as indicated by Indonesia’s corruption perception index score and its global ranking. This study aimed to analyze the criminal act of tax corruption in the aforementioned decision and to examine it from the perspective of Islamic criminal law, with a focus on the concept of jarimah taʿzīr. The research employed a qualitative method with a normative juridical approach, based on primary legal materials in the form of an analysis of the court decision and secondary legal materials in the form of books, journals, scholarly articles, and other relevant literature on Islamic law and corruption. The findings show that the defendant, Rafael Alun Trisambodo, was proven legally and convincingly to have committed corruption in the form of gratuities and Money Laundering Crimes (TPPU), for which the judge imposed a prison sentence of 14 years and a fine of IDR 1,000,000,000.00 (one billion rupiah), or six months’ imprisonment in lieu thereof. From the perspective of Islamic criminal law, corruption can be classified as jarimah taʿzīr, the sanctions for which are elastic and may be determined by judicial authorities insofar as certain elements are fulfilled. Analysis of the taʿzīr sanction concept in this decision highlights the importance of considering offender rehabilitation, proportionality, and sentencing flexibility in order to protect property (Hifz al-Mal) and uphold justice. These findings are expected to encourage the imposition of more optimal sanctions to ensure deterrence and maximize the recovery of state financial losses in future tax corruption cases.